PERAMALAN PENJUALAN JUMLAH KRIPIK DI SNACK CENTER MENGGUNAKAN METODE TRIPLE EXPONENTIAL SMOOTHING - Siti Nurul Afiyah; Nur Lailatul Aqromi (Jurnal Kajian Matematika dan Aplikasinya (JKMA), 2022)
Snack Center is a gift center that offers various kinds of products to consumers who have a lot of untapped sales transaction data to support business and services. In addition, the goods arrangement system is carried out without standardization so that the goods cannot be run. In order to make the sales process more optimal, a chip sales forecasting system was made using the triple exponential smoothing method at the Batu City Snack Center by entering the data that has been obtained. The data is the result of sales in the previous period. In the triple exponential smoothing method, three smoothing calculations are carried out, then determine the alpha value to compare the smallest error percentage level. From the results of the data that has been tested with a sales forecasting system for chips with sales data from 2020-2021, the forecast value for recommendations for the next month, namely January 2022, is 30 packs of chips at alpha parameter 0.3 with least MAPE 9.598 percent.Keywords: Chips sale, forecasting, triple exponential smoothing